Online Learning in disadvantaged areas. A Literature review - Ahmad Budidarma (Jurnal Office, 2022)
The use of technology in the era of the 4.0 technology revolution is inevitable. Even in remote areas, it is not spared in utilizing learning using technology. However, there are network constraints that limit educators and students in the learning process to form online communication. The solution expected for online learning is that the teacher prepares all forms of learning media that are ready to be studied by students, whenever and wherever they are. So that when there is an internet network students are able to learn the learning media delivered by the teacher.